From selling goods to selling services: firm responses to trade liberalization - Breinlich, Holger; Soderbery, Anson; Wright, Greg C. (American Economic Association, 2018)
In this paper we focus on a new channel of adaptation to trade liberalization, namely the shift toward increased provision of services in lieu of goods production. We exploit variation in European Union trade policy to show that lower manufacturing tariffs lead firms to shift into services provision and out of goods production. We also find that a successful transition is associated with higher firm-level R&D stocks.